The revolutionary doctrine. An interstice between the Century of Light and the chiaroscuro of revolution (2008)
The work of Goya like that of Carpentier shows the horrors of the war, in particular those taken place in the “Age of Elightenment”. Both, the painter and the writer, present their pessimistic look of the revolutionary ideals. Carpentier uses in the epigr